Konseling Holistik sebagai Dukungan Spiritual bagi Pasien Kista di RSUD Banyumas - Zabrina Naurah Valda; Muridan Muridan (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Cyst disease does not only affect patients physically, but also triggers psychological and spiritual problems such as anxiety, fear of medical procedures, emotional stress, and a crisis of life meaning during treatment. This condition indicates that cyst management should not focus solely on medical aspects, but also requires comprehensive support that addresses patients inner well-being. This study aims to analyze the role of holistic counseling as spiritual support for cyst patients at RSUD Banyumas, including its implementation and its impact on patients inner peace and spiritual resilience. This research employed a descriptive qualitative method using a case study approach. Data were collected through in-depth interviews, observation, and a review of relevant literature related to holistic counseling services and spiritual support in hospital settings. The findings show that holistic counseling provides positive effects on patients, particularly in helping them achieve emotional calmness, reduce anxiety, increase acceptance of illness, and strengthen hope and motivation to undergo treatment. Holistic counseling also supports patients in finding meaning in their suffering, which contributes to improved psychological and spiritual quality of life. However, the implementation of holistic counseling still faces several challenges, including limited time of health workers, suboptimal integration of spiritual services within the hospital system, and unequal competency among staff in providing spiritual-based counseling.